Analysis of prospects and problems in the development of human resources for the employment of Ukrainian refugees - Ilona, Polents; Dvorakova, Zuzana (Edelweiss Applied Science and Technology, 2024)
An influx of workers who have accumulated knowledge in labor markets other than the current one can have particularly large effects on the development of the host country's human resources. Other things being equal, a region with higher fluctuations in the number of highly skilled workers should be in a better position than a region with low mobility. Refugee laws are in constant evolution, reflecting the changing political, economic, and legal environments. This paper examines the situation that has developed in the Czech Republic after the arrival of a large number of refugees from Ukraine, in terms of their opportunities and prospects, as well as their ability to enter the labor market in accordance with their education and previous professional activities. The purpose of this study is to analyse the potential and obstacles to the labor integration of Ukrainian refugees, given the situation of uncertainty and the measures taken by the Czech government and state structures to receive refugees. The article considers the objective and subjective prerequisites for the labor integration of refugees, taking into account their socio-demographic characteristics and subjective intentions for the future.